When the Media Omits or Includes Scientific Evidence in Its Publications: Science and Battles on X about Child Sexual Abuse - Ane Olabarria; Ana Burgués-Freitas; Ane López de Aguileta; Harkaitz Zubiri-Esnaola; Elisabeth Torras-Gómez; Mar Joanpere; Garazi López de Aguileta; Garazi Álvarez-Guerrero; Emilia Aiello; Cristina Pulido; Gisela Redondo-Sama (Children, 2023)
Scientific evidence of social impact demonstrates how violence against children is successfully prevented. Currently, the scientific research on social impact has a focus on the analysis of actions that succeed in the implementation of such scientific evidence. This article is based on scientific research that looks at which media actions help or hinder the implementation of evidence-based actions to solve the most sensitive social problems. The social media analytics methodology has identified the posts and reposts generated during two consecutive days by news articles published by three newspapers about the official report on child sexual abuse in Spain. Their analyses have been made through communicative methodology, including voices of adult victims or survivors of child sexual abuse. The results indicate that media information that omits scientific evidence of social impact provokes battles between diverse ideological groups, while information based on scientific evidence of social impact generates consensus among people from different ideologies and actions oriented to overcome the problem.